Cognitive radio vs intelligent antenna - Mat Nawi, Siti Rabani; Toha, Nurul Farhah; Abdullah, Khaizuran; Islam, Md. Rafiqul; Khan, Sheroz (IIUM Press, 2011)
Mobile radio systems have shown rapid growth and hence have increased the awareness for more efficient use of spectrum. With the advancements of technology, the development of radio systems which are dynamic and efficient in terms of spectrum usage can be realised. Cognitive radio coined by Joseph Mitola is one of the advancements which may enhance the adaptive capabilities of radio systems and may contribute to more efficient, versatile and flexible use of spectrum. It is based on software defined radio with added intelligent signal processing, ideally based on logic, analysis and intuition, though early cognitive radios need not meet that level of sophistication. Cognitive radio has the ability to sense its surrounding environment and detect spectrum holes or white spaces, namely unoccupied frequencies, which it can use, rather than a fixed frequency assigned to it by the spectrum manager or regulator, as is currently the case